Biogeochemical shifts and zooplankton responses in post-CAAA northeastern lakes: The success of acid recovery, complexity of biological recovery, and value of long-term monitoring. (1st February 2023) - Dykema, S.; Nelson, S.J.; Hovel, R.; Saros, J.E.; Fernandez, I.J.; Webster, K.E.
Abstract: Lakes in the northeastern U.S., as in other regions, experienced significant declines in water quality and ecosystem health in the mid to late 20th century as atmospheric deposition from industrial emissions caused surface waters to acidify. After the Clean Air Act Amendments of 1990 enhanced regulations to limit emissions of sulfur and nitrogen, many lakes in the Northeast recovered from acidification. The organisms that inhabit lakes are susceptible to these shifts, and zooplankton can serve as valuable indicators of lake ecosystem responses to shifts due to their position as primary consumers in the food web. We evaluated a large historical dataset from the U.S. Environmental Protection Agency (EPA) Eastern Lake Survey (ELS) of 143 lakes throughout the northeastern U.S. to understand how recovery from acidification and subsequent chemical changes influenced zooplankton body size and community composition. We observed significant changes in chemistry; surface water sulfate concentrations decreased by 22% in the ELS lakes between the two sample years of 1986 and 2004. Increasing concentrations of DOC are common from the combined influence of deacidification and climate change, and the ELS lakes experienced a 26% increase in DOC. Notably, in the more developed regions of our study area, chloride concentration in lakes tripled, likely due to increased use of road deicers, and this is related to a subsequent increase in calcium and magnesium base cations. Zooplankton body size increased significantly between 1986 and 2004 across all taxa, and body size of Daphnia species, which require higher amounts of calcium than other zooplankton taxa, was positively associated with high calcium lakes. Shifts in zooplankton community structure, however, were most strongly influenced by variation in ANC, sulfate, and DOC. Our findings indicate that, while surface water acidity has a strong influence on zooplankton community structure, zooplankton populations are likely on a different trajectory than a simple recovery due to multiple chemical changes, such as increased chloride, occurring in lakes undergoing acid recovery. These, along with changes in climate and land-use, elicit multiple simultaneous responses in zooplankton communities. Graphical abstract: Zooplankton images: Integration and Application Network (ian.umces.edu/media-library). Image 1 Highlights: In 143 lakes sulfate declined 22% from 1986 to 2004, signifying acidification recovery. Chloride and calcium increased in lakes near roads and development. Zooplankton size increased overall; Daphnia size increased with calcium. Lake acidity affected zooplankton community structure in 2004 cross-lake comparison. Novel climate, land use, and chemistry preclude return to pre-acidification status.